Training terms and strategies
Basic infiormation for middle distance runners on: - Aerobic Conditioning: Building the Foundation - Anaerobic Conditioning: Raising the Threshold - Aerobic Capacity Training: Increasing Your V02 Max - Anaerobic Capacity Training: Teaching Your Body to Buffer Lactic Acid